Pharmacological Therapy in Smoking Cessation - Mahmood, Manzoor; Hoque, Harisul; Rahman, Md Mukhlesur; Zaman, SM Mustafa; Salim, Md Abu; Arzu, Jahanara; Adhikary, Dipal Krishna (University Heart Journal, 2014)
No abstract. DOI: http://dx.doi.org/10.3329/uhj.v9i1.19509 University Heart Journal Vol. 9, No. 1, January 2013; 33-39